Battling the devolution in the research on corporate philanthropy - Liket, K. (2015)
The conceptual literature increasingly portrays corporate philanthropy (CP) as an old-fashioned and ineffective operationalization of a firm’s corporate social responsibility. In contrast, empirical research indicates that corporations of all sizes, and both in developed and emerging economies, actively practice CP. This disadvantaged status of the concept, and research, on CP, complicates the advancement of our knowledge about the topic. In a systematic review of the literature containing 122 journal articles on CP, we show that this business practice is loaded with unique characteristics, strengths, and weaknesses, and both conceptual and practical challenges that require renewed attention. We identify six interrelated but distinctive research themes in the literature: concept, motives, determinants, practices, business outcomes, and social outcomes. Dividing the literature on CP into six research themes creates an insightful comprehensive map of this intellectual terrain. Moreover, we distinguish among the level at which CP is analyzed: individual, organizational, institutional, or any combination of these levels. The review reveals significant gaps in the knowledge on CP. Most importantly we find that the conceptualization is limited, the research is mostly quantitative, the effects of CP on society are severely under-researched, and there is a lack of multilevel analyses. A detailed future research agenda is offered, including specific suggestions for research designs and measurements.